Prevalence and genetic identification of bucephalid cercariae from the golden mussel (Limnoperna fortunei) in Northern Vietnam - Le Hung, Anh; Nguyen, Van Ha; Nguyen Ngoc, Chinh; Atopkin, Dmitry M.; Simonova, Nadezhda; Duc Vu, Manh; Minh Anh, Kim; Manh Nguyen, Hung (Academia Journal of Biology, 2026)
A total of 1,453 specimens of the golden mussel Limnoperna fortunei were collected by handpicking from cultured areas of channel catfish (Ictalurus punctatus) in Son La, Hoa Binh, Thac Ba reservoirs, and from the Duong River, and examined for trematode infection. Of these, 178 specimens were found to shed bucephalid cercariae. The infection rate in the Duong River was 3.14 times higher than that of the reservoirs (p = 0.005), while no significant differences were observed among the reservoirs. Based on 28S rDNA sequence analysis, three trematode species were identified, including Dollfustrema bagarii and two species of the genus Prosorhynchoides.